Cytokine Signature Induced by SARS-CoV-2 Spike Protein in a Mouse Model - Gu, Tingxuan; Zhao, Simin; Jin, Guoguo; Song, Mengqiu; Zhi, Yafei; Zhao, Ran; Ma, Fayang; Zheng, Yaqiu; Wang, Keke; Liu, Hui; Xin, Mingxia; Han, Wei; et al. (Frontiers in Immunology, 2021)
Although COVID-19 has become a major challenge to global health, there are currently no efficacious antiviral agents or vaccines. Cytokine storm syndrome (CSS) can lead to acute respiratory distress syndrome (ARDS), which contributes to most COVID-19 mortalities. Research points to interleukin 6 (IL-6) as a crucial signature of the cytokine storm, and the clinical use of the IL-6 inhibitor tocilizumab shows potential for treatment of COVID-19 patient. In this study, we challenged wild-type and adenovirus-5/human angiotensin-converting enzyme 2-expressing Balb/c mice with a combination of polyinosinic-polycytidylic acid and recombinant SARS-CoV-2 spike-extracellular domain protein. High levels of TNF-α and near 100 times increased IL-6 were detected at 6 h, but disappeared by 24 h in bronchoalveolar lavage fluid (BALF) following immunostimulant challenge. Lung injury observed by histopathologic changes and magnetic resonance imaging at 24 h indicated that increased TNF-α and IL-6 may initiate CSS in the lung, resulting in the continual production of inflammatory cytokines. We hypothesize that TNF-α and IL-6 may contribute to the occurrence of CSS in COVID-19. We also investigated multiple monoclonal antibodies (mAbs) and inhibitors for neutralizing the pro-inflammatory phenotype of COVID-19: mAbs against IL-1α, IL-6, TNF-α and granulocyte-macrophage colony-stimulating factor (GM-CSF), and inhibitors of p38 and JAK partially relieved CSS; mAbs against IL-6, TNF-α and GM-CSF, and inhibitors of p38, extracellular signal-regulated kinase and myeloperoxidase somewhat reduced neutrophilic alveolitis in the lung. This novel murine model opens a biologically safe, time-saving avenue for clarifying the mechanism of CSS/ARDS in COVID-19 and developing new therapeutic drugs.